Predicting Intention to Use Nicotine Replacement Therapy in People Attending Residential Treatment for Substance Dependence. Issue 2 (3rd April 2018) - Kelly, Peter J.; Townsend, Camilla J.; Osborne, Briony A.; Baker, Amanda L.; Deane, Frank P.; Keane, Carol; Ingram, Isabella; Lunn, Joanne
Abstract: Objective: Nicotine replacement therapy (NRT) is recommended as a frontline smoking cessation tool for people attending mental health and substance dependence treatment services. Previous research suggests that NRT is underutilized in these settings. To improve the use of NRT among people attending residential treatment for substance use disorders, it is important that the factors influencing smokers' decisions to use NRT are understood. The study aimed to examine (1) smoking cessation strategies used by participants in previous quit attempts, (2) participants' attitudes toward NRT (i.e., safety concerns and perceived efficacy), and (3) the predictors of participants' intention to use NRT to support future quit attempts.Methods: Participants completed a cross-sectional survey that examined their smoking behaviors, previous experiences using smoking cessation strategies, attitudes and beliefs regarding NRT, and intention to use NRT as part of future quit attempts ( N = 218). All participants were attending residential treatment for substance use disorders provided by We Help Ourselves, a large provider of specialist alcohol and other drug treatment in Australia.Results: The majority of respondents (98%) reported that they had smoked regularly in their lifetime, and 89% were current smokers. Forty-five percent of the current smokers reported that they had previously used NRT to support a quit attempt, with 54% reporting that they intended to use NRT to support a future quit attempt. Intentions to use NRT were not related to the participants' mental health status or the participants' perceptions regarding the safety or potential drawbacks associated with using NRT. However, participants were more likely to report that they would use NRT to support future quit attempts if they were female, had previously used NRT, and perceived NRT to be effective.Conclusions: Improving the use of evidence-based smoking cessation strategies within substance use treatment continues to be a priority. To enhance the use of NRT among consumers attending mental health and addiction treatment services, NRT should be universally offered. Future research should consider strategies that help to improve participants' positive perceptions regarding the efficacy of NRT.